FESTIVAL ISLAMIC GOOD CHILD SEBAGAI SARANA PENANAMAN NILAI RELIGIUS - Aziz, Abdul; Asiah, Siti; Rabiannur, Rabiannur (LPPM Universitas Islam 45, 2024)
Festival Islamic good child is a single work program coordinated by one of the students of Islamic University 45 Bekasi held in the village of Sirnajati. The purpose of organizing the Festival Islamic Good Child program is to enhance the enthusiasm for seeking knowledge about Islam, and cultivate interest and ability in the field of religion, and foster self-confidence in the children of Sirnajati Village. In the implementation of the Festival Islamic Good Child, there are 3 competition classes: adhan rivalry, short surah retention rivalry, and calligraphy shading. The technique of conducting training is by examining the needs of early childhood, organizing, implementing, evaluating, and following up on the training that has been conducted. The consequence of this Festival Islamic Good Child program is that the children of the Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Jamiatul Khoir in Sirnajati Village will be more enthusiastic in learning and practicing the teachings of Islam, and then the children of Sirnajati Village will also be more courageous in demonstrating their abilities and their self-confidence will increase after participating in the Festival Islamic Good Child program. This is evidenced by several youths from Sirnajati Village who initially did not want to perform the adhan, but after the Festival Islamic Good Child was held, they became fearless to perform the adhan.